2000
DOI: 10.4049/jimmunol.165.8.4372
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Receptor Expression on Human Retinal Pigment Epithelial Cells from the Blood-Retina Barrier Leads to Chemokine Secretion and Migration in Response to Stromal Cell-Derived Factor 1α

Abstract: Retinal pigment epithelial (RPE) cells form part of the blood-retina barrier and have recently been shown to produce various chemokines in response to proinflammatory cytokines. As the scope of chemokine action has been shown to extend beyond the regulation of leukocyte migration, we have investigated the expression of chemokine receptors on RPE cells to determine whether they could be a target for chemokine signaling. RT-PCR analysis indicated that the predominant receptor expressed on RPE cells was CXCR4. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 55 publications
3
49
2
Order By: Relevance
“…The variation in the level of induction of CXCR4 in NHBEs is not surprising and could be due in part to interdonor variability in the level of expression of receptors for BK and IL-1␤. In agreement with our findings, IL-1␤ has been demonstrated to elevate CXCR4 mRNA levels in human pigment epithelial cells (7). Both IL-1␤ and BK are known to activate the transcription factors NF-B and AP-1 (13)(14)(15).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The variation in the level of induction of CXCR4 in NHBEs is not surprising and could be due in part to interdonor variability in the level of expression of receptors for BK and IL-1␤. In agreement with our findings, IL-1␤ has been demonstrated to elevate CXCR4 mRNA levels in human pigment epithelial cells (7). Both IL-1␤ and BK are known to activate the transcription factors NF-B and AP-1 (13)(14)(15).…”
Section: Discussionsupporting
confidence: 92%
“…SDF-1␣ induced the production of growth-related oncogene ␣ and IL-8 by intestinal epithelial cells while monocyte chemoattractant protein 1, IL-8, and growth-related oncogene ␣ were released from retinal pigment epithelial cells after SDF-1␣ stimulation (7,18). As SDF-1␣ induces phosphorylation of several MAP kinase in NHBEs, it is highly probably that one of the outcomes of this response is the release of chemokines into the airway lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assumed that it was interaction of monocyte-macrophages and RPE cells promoting SDF-1. We thus performed in vitro monocyte-RPE co-culturing, and found that SDF-1 secretion was largely promoted by direct contact with monocytes, while SDF-1 in RPE cells cultured alone was undetectable by ELISA, similar to results reported by Isabel et al, who found that SDF-1α production by RPE cells could be detected by ELISA, but only at levels near the detection limit (1.33± 1.0 pg/ml) [44]. We also showed that direct contact with monocytes was significantly more potent for stimulating SDF-1 production in the supernatant than indirect contact through a polyporous membrane.…”
Section: Discussionsupporting
confidence: 85%
“…In this regard, two recent studies have documented the ability of SDF-1 to activate chemokine expression; SDF-1 up-regulated production of the CXC chemokines IL-8 and GRO-␣ by human colon epithelial cells (75) and MCP-1, IL-8, and GRO-␣ by human retinal pigment epithelial cells (76). These findings suggest that SDF-1 activation of chemokine expression may occur in a cell-type-specific manner.…”
Section: Discussionmentioning
confidence: 89%